Composition analysis and transition energies of ultrathin Sn-rich GeSn quantum wells - Fischer, Inga A.; Clausen, Caterina J.; Schwarz, Daniel; Zaumseil, Peter; Capellini, Giovanni; Virgilio, Michele; Figueira, Maria Cecilia Da Silva; Birner, Stefan; Koelling, Sebastian; Koenraad, Paul M.; Huang, Michael R. S.; Koch, Christoph T.; et al. (Physical Review Materials, 2020)
While GeSn alloys with high Sn content constitute direct group-IV semiconductors, their growth on Si remains challenging. The deposition of a few monolayers of pure Sn on Ge and their overgrowth with Ge using molecular beam epitaxy can be a means of obtaining Sn-rich quantum wells with very high Sn content while maintaining high crystal quality. Here, we provide structural and compositional information on such structures with very high accuracy. Based on our characterization results we theoretically predict transition energies and compare them with experimental results from photoluminescence measurements. Our results constitute the groundwork for tuning the molecular beam epitaxy based growth of Sn-rich quantum wells and dots for applications in electronic and optoelectronic devices.
CRIS-Team Scopus Importer:2021-06-29